Implementation of Zuhd in the Islâh Movement of Shaykh Abdul Qadir al-Jilani (D. 521-561 H) - Ihsan, Nur Hadi; Mudin, Moh. Isom; Sahidin, Amir (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
The issue of zuhd is very urgent to deal with, especially in the current era of modernization which has had negative impacts in all fields; in education, social, political, and cultural. Therefore, an islâh movement is needed to minimize and even eliminate these negative impacts. Among the Sufi scholars who were very persistent in implementing the islâh movement was Shaykh Abdul Qadir al-Jilani. At a time when there was a lot of depravity and shocks in his time, al-Jilani with his zuhd was able to play a good role in this islâh movement. Therefore, this article will specifically discuss the implementation of zuhd in the islâh movement of Shaykh Abdul Qadir al-Jilani. Using the descriptive-analytical method, this study finds that the implementation of zuhd in the islâh movement of al-Jilani includes three things, namely in interpreting the true meaning and understanding of zuhd; in education and teaching, as well as in his lectures and preaching. Thus, al-Jilani was one of the Sufi scholars who integrated the teaching of zuhd with his islâh movements. Finally, it seems justifiable to assert that integrating zuhd with the islâh movement is very important to overcome the destructive impacts of modernization. Masalah zuhd sangat urgen untuk dibahas, terutama di era modernisasi saat ini yang telah membawa dampak negatif di segala bidang; baik pendidikan, sosial, politik, maupun budaya. Oleh karena itu, diperlukan gerakan islâh untuk meminimalisir bahkan menghilangkan dampak negatif tersebut. Di antara ulama sufi yang sangat gigih dalam melaksanakan gerakan islâh adalah Syekh Abdul Qadir al-Jilani. Di saat banyak kerusakan dan goncangan pada masanya, al-Jilani dengan zuhdnya mampu berperan dengan baik dalam gerakan islâh ini. Oleh karena itu, artikel ini secara khusus akan membahas implementasi zuhd dalam gerakan islâh Syekh Abdul Qadir al-Jilani. Melalui kajian diskriptif analitik terhadap berbagai literatur yang otoritatif, ditemukan bahwa implementasi zuhd dalam gerakan islâh al-Jilani meliputi tiga hal, yaitu dalam memaknai zuhd yang benar; dalam pendidikan dan pengajaran, serta dalam ceramah dan dakwahnya. Dengan demikian, al-Jilani merupakan salah seorang ulama sufi yang mengintegrasikan makna zuhd dengan gerakan islâhnya. Akhirnya, berdasarkan temuan ini dapat dibenarkan bahwa integrasi zuhd dengan gerakan islâh merupakan hal yang sangat penting untuk mengatasi dampak buruk modernisasi.